Intratumoral Lentivector-Mediated TGF-β1 Gene Downregulation As a Potent Strategy for Enhancing the Antitumor Effect of Therapy Composed of Cyclophosphamide and Dendritic Cells - Rossowska, Joanna; Anger, Natalia; Szczygieł, Agnieszka; Mierzejewska, Jagoda; Pajtasz-Piasecka, Elżbieta (Frontiers in Immunology, 2017)
Vaccination with dendritic cells (DCs) stimulated with tumor antigens can induce specific cellular immune response that recognizes a high spectrum of tumor antigens. However, the ability of cancer cells to produce immunosuppressive factors drastically decreases the antitumor activity of DCs. The main purpose of the study was to improve the effectiveness of DC-based immunotherapy or chemoimmunotherapy composed of cyclophosphamide (CY) and DCs by application of lentivectors (LVs)-encoding short hairpin RNA specific for TGF-β1 (shTGFβ1 LVs). We observed that s.c. inoculation of both MC38 cells with silenced expression of TGF-β1 (MC38/shTGF-β1) and direct intratumoral application of shTGFβ1 LVs contributed to reduction of suppressor activity of myeloid cells and Tregs in tumor. Contrary to expectations, in mice bearing wild tumor, the application of shTGFβ1 LVs prior to vaccination with bone marrow-derived DC stimulated with tumor antigens (BMDC/TAg) did not influence myeloid-derived suppressor cell (MDSC) infiltration into tumor. As a result, we observed only minor MC38 tumor growth inhibition (TGI) accompanied by systemic antitumor response activation comparable to that obtained for negative control (shN). However, when the proposed scheme was complemented by pretreatment with a low dose of CY, we noticed high MC38 TGI together with decreased number of MDSCs in tumor and induction of Th1-type response. Moreover, in both schemes of treatment, LVs (shTGFβ1 as well as shN) induced high influx of CTLs into tumor associated probably with the viral antigen introduction into tumor microenvironment. Concluding, the application of shTGFβ1 LVs alone or in combination with DC-based vaccines is not sufficient for long-lasting elimination of suppression in tumor. However, simultaneous reduction of TGF-β1 in tumor microenvironment and its remodeling by pretreatment with a low dose of CY facilitates the settlement of peritumorally inoculated DCs and supports them in restoration and activation of a potent antitumor response.